The The Liquidity Issues and the Profitability Index of Small-Scale Business Entities in Sorsogon Province, Philippines - Bongalonta, Michael B.; Bongalonta, Michelle M. (Future Science / FSH-PH Publications, 2022)
This research was conducted to determine the liquidity issues and profitability index of small-scale businesses operating in the Second District of Sorsogon Province, Philippines as well as to establish the relationship of these two variables. This study used mixed design. A total of 223 small-scale business owners engaged in trading in the Second District of Sorsogon Province, Philippines were the primary respondents of this research. Vertical analyses and stepwise linear regression analyses were utilized. This study concludes that small-scale business entities in the Province of Sorsogon are highly liquid and profitable depicting their ability to pay short-term maturing obligation. Limited and unavailability of capitalization, Absence of Credit Policy, High Finance cost for debt financing, Inventory obsolescence, Shortage of resources and Lack of markets of measure and scope are the identified liquidity issues by small-scale business owners. To address the issues, the Use equity financing than debt financing, Strengthen the company’s policy of extending loan, Minimize the purchase of inventory or stocks, financial suffering by staying well-informed of your finances and Hiring Bookkeepers are highly recommended by the respondents.